1996
DOI: 10.1007/bf02353490
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic conjugation/deconjugation cycling pathways. Computer simulations examining the effect of michaelis-menten parameters, enzyme distribution patterns, and a diffusional barrier on metabolite disposition

Abstract: Conjugation/deconjugation cycling plays an important role in the physiologic regulation of the concentration of endogenous compounds that form conjugated metabolites. Less is known concerning the deconjugation of xenobiotics. The model compound p-nitrophenol (pNP) is conjugated to sulfate and glucuronide metabolites which can also undergo hydrolysis, via separate enzyme systems, to regenerate pNP. In the present investigation, computer simulations were performed using literature values for the KM and Vmax for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…8,9 Diffusion-limited entry was implied to exist for 4MUS in single-pass perfused liver studies, 4,10 and would reduce the net removal and extraction ratio of the compound. 9 In contrast, the biliary excretion clearances of 4MUS, as a preformed species or as a metabolite of 4MU, were found to be similar in perfused rat liver studies performed in our laboratory 8 ; the observation points toward the rapid equilibration of 4MUS across the sinusoidal membrane. Concentrationdependent hepatocellular entry of 4MUS was subsequently found in isolated rat hepatocytes.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…8,9 Diffusion-limited entry was implied to exist for 4MUS in single-pass perfused liver studies, 4,10 and would reduce the net removal and extraction ratio of the compound. 9 In contrast, the biliary excretion clearances of 4MUS, as a preformed species or as a metabolite of 4MU, were found to be similar in perfused rat liver studies performed in our laboratory 8 ; the observation points toward the rapid equilibration of 4MUS across the sinusoidal membrane. Concentrationdependent hepatocellular entry of 4MUS was subsequently found in isolated rat hepatocytes.…”
mentioning
confidence: 69%
“…8 The extent of futile cycling is expected to be modulated by the mode of hepatocellular entry of the precursor-product pair. 8,9 Diffusion-limited entry was implied to exist for 4MUS in single-pass perfused liver studies, 4,10 and would reduce the net removal and extraction ratio of the compound. 9 In contrast, the biliary excretion clearances of 4MUS, as a preformed species or as a metabolite of 4MU, were found to be similar in perfused rat liver studies performed in our laboratory 8 ; the observation points toward the rapid equilibration of 4MUS across the sinusoidal membrane.…”
mentioning
confidence: 99%
“…Extensive pharmacokinetic studies have shown that stevioside is absorbed as steviol (Fig. 1) in different animal species 3–9 . Steviol is the core structure of stevioside and it may be the active part that is responsible for the therapeutic effects of stevioside.…”
Section: Introductionmentioning
confidence: 99%
“…1) in different animal species. [3][4][5][6][7][8][9] Steviol is the core structure of stevioside and it may be the active part that is responsible for the therapeutic effects of stevioside. It has been proposed that steviol may be developed for therapeutic purposes.…”
mentioning
confidence: 99%